A Retrospective Study of the Dosimetric Parameters and Duodenal Toxicity in Patients With Upper Gastrointestinal and Gynaecological Cancers Treated With Radiation Therapy. Issue 2 (February 2020) - George, G.; Lewis, S.; Chopra, S.; Phurailatpam, R.; Engineer, R.
Abstract: Aims: The duodenum is a critical organ at risk while planning radiation for gastrointestinal cancers or para-aortic nodes from gynaecological cancers due to the close proximity to the target volumes. The aim of this study was to assess the dosimetric parameters of the duodenum received during radiotherapy to upper gastrointestinal and gynaecological malignancies and their correlation with clinical toxicity. Materials and methods: All adult patients who were treated with radiotherapy for primary upper gastrointestinal cancers (liver, stomach, pancreas, gall bladder) and patients with gynaecological cancers who were treated with extended fields in view of para-aortic nodal involvement from 1 January 2010 to 31 July 2015 were considered for the study. The radiation dose prescription was 45 Gy to the elective clinical target volume and 52.5–60 Gy to the gross nodal volume. The planning computed tomography scan was retrieved and the dose–volume histogram parameters for the duodenum were extracted. The relative volumes of duodenum receiving a dose from 40 to 55 Gy in increments of 5 Gy (V40Gy, V45Gy, V50Gy, V55Gy) were also noted. Results: Of the 258 patients assessed, 30 patients (12.1%) were detected to have grade 2–4 toxicities related to the duodenum as detected on endoscopy. Most had grade 3 toxicity – 18 patients were diagnosed with grade 3 toxicity and four patients had grade 4 toxicity. The most common toxicity noted was duodenal ulceration seen in 16 patients. The other toxicities were duodenal stricture in eight patients, duodenal perforation in five patients and one patient was reported to have duodenal fistula. The patients with duodenum receiving V55Gy ≥ 1 cm 3 (7.7% versus 3.8%, P  = 0.014) and V50Gy ≥ 4 cm 3 (7.7% versus 3.8%, P  = 0.014) had higher grade ≥2 duodenal toxicity. Conclusion: A threshold level of V55Gy ≥ 1 cm 3 and V50Gy ≥ 4 cm 3 for the duodenum is predictive of clinically significant grade 2 and higher toxicity and could serve as valid dose constraints for the duodenum. Highlights: The duodenum is a critical organ at risk during planning radiotherapy for the upper abdomen. This study evaluated the dose–volume parameters for the duodenum in patients treated with radiation. A positive correlation of V55Gy ≥ 1cm 3 and V50Gy ≥ 4 cm 3 was seen with grade 2 and higher duodenal toxicity.